The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4491/eer.2016.019
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies using a linear regression analysis for a sorption phenomenon of 17a-methyltestosterone by Salvinia cucullata in an active plant reactor

Abstract: The aim of this study was to investigate the removal efficiency of 17α-methyltestosterone (MT) from aqueous solution by Salvinia cucullata Roxb. ex Bory in an active plant-based reactor with a specific focus on linear regression analysis for the sorption phenomena of MT onto the plant roots. A high performance liquid chromatographic method using UV detection (245 nm) was used to analyse the samples. The batch experiments of the active plant reactor (APR) were established to investigate the ability of Salvinia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It indicated that the process was done chemically. The mechanism that occurred in PO 4 -P removal in other studies indicated that phosphorus removal referred to the The second-order kinetic model could also be applied to the ammonium nitrogen removal using constructed wetlands (Zhu et al, 2011) and 17α-methyltestosterone removal with Salvinia cucullata (Adnan and Thanasupsin, 2016).…”
Section: Kinetics Modelmentioning
confidence: 99%
“…It indicated that the process was done chemically. The mechanism that occurred in PO 4 -P removal in other studies indicated that phosphorus removal referred to the The second-order kinetic model could also be applied to the ammonium nitrogen removal using constructed wetlands (Zhu et al, 2011) and 17α-methyltestosterone removal with Salvinia cucullata (Adnan and Thanasupsin, 2016).…”
Section: Kinetics Modelmentioning
confidence: 99%
“…In light of the information presented in the literature, adsorption on a heterogeneous surface is most often described by the following models: pseudo first-order and pseudo second-order kinetic models (PFO and PSO), intraparticle diffusion model (Weber-Morris), and chemisorption on a heterogeneous surface (Elovich) [13][14][15][16]. However, a commonly used tool for the analysis of empirical data is linear regression, and the classic method of least squares is used to determine the optimal values of unknown parameters [17][18][19][20][21]. Nevertheless, the greatest disadvantage of the above method is the undefined distribution of empirical data errors when determining the parameters of a given model, as a result of transforming kinetic equations into linearized forms.…”
Section: Introductionmentioning
confidence: 99%
“…In the light of the information presented in the literature, adsorption on a heterogeneous surface is most often described by the following models: pseudo first-order and pseudo second-order kinetic models (PFO and PSO), intraparticle diffusion model (Weber-Morris), and chemisorption on a heterogeneous surface (Elovich) [13][14][15][16]. However, a commonly used tool for the analysis of empirical data is linear regression, and the classic method of least squares is used to determine the optimal values of unknown parameters [17][18][19][20][21]. Nevertheless, the greatest disadvantage of the above method is the undefined distribution of empirical data errors when determining the parameters of a given model, as a result of transforming kinetic equations into linearized forms.…”
Section: Introductionmentioning
confidence: 99%